Self-Assembly, Thermotropic, and Lyotropic Phase Behavior of Guerbet Branched-Chain Maltosides - Saari, Nur Asmak Nabila; Mislan, Azwa Amanina; Hashim, Rauzah; Zahid, Noor Idayu Mat (American Chemical Society, 2018)
Five synthetic β-d-maltosides derived from Guerbet branched alcohols, whose total hydrocarbon chain length ranged from C8 to C24, were synthesized to a high anomeric purity, and their thermal properties, liquid-crystalline phases, and structures were characterized using differential scanning calorimetry, optical polarizing microscopy, and small-angle X-ray scattering. Thermal investigations of all anhydrous Guerbet maltosides showed that they do not form solid crystals but undergo a glass transition upon temperature change in the range of 35-53 °C. The glassy crystalline structure turns into the liquid-crystalline structure upon heating or addition of water. In thermotropic studies, the lamellar phase formation is prominent in shorter-chain-length analogues, whereas the longer-chain compounds exhibit a more frustrated form of self-assembly in the formation of a metastable state, polymorphism, and inverse bicontinuous cubic structure (Ia3d). The excess water conditions show that the phase formation is dominated by the lamellar phase for the longer-chain compounds. Normal micellar solution was observed in the shortest-chain-length maltosides because of the enlargement of hydrated maltose headgroups. The self-assembly of both dry and fully hydrated Guerbet maltosides, which exhibited glass-forming abilities and showed surface activity and also the ability to act as membrane-stabilizing compounds, makes them ideal candidates for practical use in industry as well as biomedical research.